2011
DOI: 10.1007/s00381-011-1495-9
|View full text |Cite
|
Sign up to set email alerts
|

Palliative functional hemispherectomy for treatment of refractory status epilepticus associated with Alpers' disease

Abstract: Functional hemispherectomy was effective for the treatment of refractory status epilepticus in Alpers' disease. We believe that the procedure resulted in improved quality of life which was the primary outcome goal. Palliative procedures should be considered in diseases with ultimate fatal outcome when the short-term benefits outweigh the risks. The ethical aspects of treatment must be carefully considered to insure treatment is provided in the best interest of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…Possible efficacious treatments for seizure were identified in 18 cases: ketogenic diet/low glycemic diet (n = 3), phenobarbital (n = 3), combined midazolam and thiopentone with other AEDs (n = 2), magnesium infusion (n = 2), combined propofol and thiopentone (n = 1), ketamine infusion (n = 1), folinic acid (n = 1), and carnitine for hepatic encephalopathy (n = 1) (Table ). Palliative hemispherectomy was performed in a single patient . A case series consisting entirely of adult patients with POLG ‐related occipital epilepsy (n = 19) suggested that a combination of sodium channel blocker (carbamazepine, oxcarbazepine, lamotrigine, and phenytoin) and benzodiazepine was effective for generalized tonic–clonic seizure, whereas myoclonus was better controlled with topiramate, phenobarbital, or clonazepam …”
Section: Resultsmentioning
confidence: 99%
“…Possible efficacious treatments for seizure were identified in 18 cases: ketogenic diet/low glycemic diet (n = 3), phenobarbital (n = 3), combined midazolam and thiopentone with other AEDs (n = 2), magnesium infusion (n = 2), combined propofol and thiopentone (n = 1), ketamine infusion (n = 1), folinic acid (n = 1), and carnitine for hepatic encephalopathy (n = 1) (Table ). Palliative hemispherectomy was performed in a single patient . A case series consisting entirely of adult patients with POLG ‐related occipital epilepsy (n = 19) suggested that a combination of sodium channel blocker (carbamazepine, oxcarbazepine, lamotrigine, and phenytoin) and benzodiazepine was effective for generalized tonic–clonic seizure, whereas myoclonus was better controlled with topiramate, phenobarbital, or clonazepam …”
Section: Resultsmentioning
confidence: 99%
“…There is a precedent for palliative hemispherectomy surgery. Lupashko and colleagues reported on a child with a terminal condition (Alper’s disease) and refractory status epilepticus that underwent hemispherectomy for palliation to allow extubation and hospital discharge 33 . Ciliberto and colleagues reported on 7 patients with clearly defined bilateral seizure onset undergoing hemispherectomy surgery with three patients achieving seizure freedom (Engel I), and all patients with subjectively improved quality of life 34 .…”
Section: Discussionmentioning
confidence: 99%
“…59 However, VNS was not associated with significant seizure reduction in 5 children with biochemically but not genetically confirmed mitochondrial disease. 61 However, she died of liver failure only a few months later, so it is debatable whether such an invasive procedure was justified given the ultimately fatal outcome. 61 However, she died of liver failure only a few months later, so it is debatable whether such an invasive procedure was justified given the ultimately fatal outcome.…”
Section: Managementmentioning
confidence: 99%
“…60 Palliative functional hemispherectomy was reported to allow a child with Alpers syndrome and refractory status epilepticus to be extubated and discharged home. 61 However, she died of liver failure only a few months later, so it is debatable whether such an invasive procedure was justified given the ultimately fatal outcome. 62,63 In patients with status epilepticus, treatment of the underlying disease is clearly important.…”
Section: Managementmentioning
confidence: 99%